Has regulatory capital made banks safer? Skin in the game vs moral hazard - Ernest Dautovic (European Central Bank (ECB), 2020)
The paper evaluates the impact of a phased-in introduction of capital requirements on equity, risk-taking, and probability of default for a sample of European systemically important banks. Contrary to the case of a one-off introduction of capital requirements, this study does not find evidence of deleveraging through asset sales. A phased-in tightening promotes adjustment to lower leverage via an increase in equity thereby improving resilience and loss absorption capacity. The higher resilience comes at the cost of a portfolio reallocation towards riskier assets. Consistently with models on agency costs and gambling for resurrection, the risk-taking is driven by large and less profitable banks. The net impact on bank probabilities of default is positive albeit statistically insignificant, suggesting that risk-taking may crowd-out solvency.
Keywords: E51; G21; G28; O52; 330; capital requirements; macroprudential policy; risk-taking; impact evaluation; difference-in-difference